Fashion Design Competitions as an Important Component of the Representation of Students’ Creativity (Experience of the Department of Fabric and Clothing Design of the KSADA) - Gurdina, Vladyslava (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article examines previous studies on the formation and development of the fashion industry in Ukraine, with particular attention to specialized competitions for young fashion designers. It is established that competition practices remain insufficiently reflected in the scientific literature, especially in recent years. The importance of students’ participation in such events is emphasized, as they are seen as a bridge between the educational process and professional realization. Competitions contribute not only to the professional growth of young designers, but also to the development of creative potential, self-presentation, and integration into the professional environment. The study identifies the most notable fashion design competitions in Ukraine in the 21st century and traces the transformation of their formats over the past five years, during which many activities shifted to online formats due to the pandemic and military circumstances. The analysis highlights several problems of online competitions, including the absence of direct communication, networking, and live feedback, as well as the lack of prize funds, all of which reduce students’ motivation to participate. On the basis on the author’s own experience as a curator of a competition for young designers, the study tests new approaches to organizing professional competitions that motivate participants, provide feedback, facilitate the acquisition of new knowledge, and foster professional connections. Promising directions are identified, including inclusive nominations alongside ecological and digital design. The article also provides specific examples of the participation and achievements of students from the Department of Fabric and Clothing Design of the Kharkiv State Academy of Design and Arts in national and international competitions. Selected works that achieved the highest results are described and illustrated.